1985
DOI: 10.1007/bf02148888
|View full text |Cite
|
Sign up to set email alerts
|

Microproliferations in proliferative diabetic retinopathy and their relationship to the vitreous: corresponding light and electron microscopic studies

Abstract: Using a special embedding method, autopsied eyes with proliferative diabetic retinopathy were studied. In areas with no posterior vitreous detachment, small proliferations may arise multifocally and grow within the vitreous cortex. The fibrous material of the vitreous cortex is densely interconnected with and obviously incorporated into the newly formed proliferated tissue, a process which causes coarse traction lines on the vitreous cortex lamellae. The clinical consequences of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 14 publications
0
30
0
3
Order By: Relevance
“…Conversely, 'complete' PVD protects against proliferative diabetic retinopathy, 51 because the newly formed blood vessels require the collagenous network of the cortical vitreous as a scaffold for growth and invasion. 52 In the presence of a PVD or following surgical vitrectomy, abortive neovascular outgrowths have been observed in the eyes of diabetic patients. 51 …”
Section: Morphology Of the Vitreousmentioning
confidence: 99%
“…Conversely, 'complete' PVD protects against proliferative diabetic retinopathy, 51 because the newly formed blood vessels require the collagenous network of the cortical vitreous as a scaffold for growth and invasion. 52 In the presence of a PVD or following surgical vitrectomy, abortive neovascular outgrowths have been observed in the eyes of diabetic patients. 51 …”
Section: Morphology Of the Vitreousmentioning
confidence: 99%
“…These membranes are essentially neovascular in nature and their relationship to the ILM is impossible to assess on surgically excised membrane peel specimens. This issue has however been elegantly addressed on postmortem eyes by Faulborn et al 35 Their celloidin-embedded samples showed these vascular membranes present within the vitreous cortex. In our series, we were unable to identify ILM in any PDR cases.…”
Section: Cadaver Eyesmentioning
confidence: 99%
“…Several clinical and experimental studies have demonstrated that the vitreous plays a primary role in the pathogenesis of PDVR. The studies have shown the presence of new vessels microproliferating inside the vitreous cavity, indicating the vitreous to be active in the angiogenesis process [34]. There is also evidence that epiretinal membranes in the vitreous of patients with PDVR produce a high amount of growth factors as the retinal cells do [43, 44, 46, 79].…”
Section: Hypothetical Pathogenesis Of Pdvrmentioning
confidence: 99%
“…The instability of the vitreous resulting from this loss of the gel state without dehiscence at the vitreoretinal interface may also induce traction on the retina, which in turn might not only lead to retinal tears but can also contribute to the neovascular process itself. Thus, in addition to providing a scaffold for retinal capillary endothelial and other vasoproliferative cells as postulated by Faulborn and Bowald in 1985 [34], the vitreous may aggravate the process of neovascularization because of changes in the rheologic state.…”
Section: Hypothetical Pathogenesis Of Pdvrmentioning
confidence: 99%
See 1 more Smart Citation